IMPORTANCE OF BRAND POSITIONING IN SMES - Elizabeth Pico Leiva, Cinthia; Antonella Cañete Benítez, Gabriela; Martin Paniagua González, Pablo; A. Dávalos Giménez, Luis (Revista Gênero e Interdisciplinaridade, 2023)
The objective of this work is to gain knowledge about the Importance of brand positioning in SMEs. The research was carried out with a quantitative approach. The level of research used is descriptive, the information obtained allowed us to draw conclusions to understand the situations of SMEs. To understand the result, a questionnaire with closed questions was posed, which will verify the importance of brand positioning in SMEs. The results were expressed through tables and graphs with their respective percentages.